The proteomic analysis of leaf in Rapeseed (Brassica napus L) under salt stress - Nima Dolatabadi (مجله بیوتکنولوژی کشاورزی, 2018)
Salinity is one of the most important problems in arid and semi-arid areas that causes serious decrement in agricultural productions. Rapeseed is a superior oilseed due to the high quality of oil, large amounts of polyunsaturated fatty acids and oil yield. To deal with abiotic stress conditions, plants synthesize some essential metabolites, special structural proteins or metabolic enzymes pathways to overcome the stress. To identify the molecular mechanisms of salt responsiveness in rapeseed, proteome changes of Option500 a salt-sensitive genotype under salt stress was studied. An increase in proline and the Na+ of leaf and a reduction in shoot dry weight, plant height, K+ and K+/Na+ were observed under salt stress (0, 150, 300 mM). Over 110 protein spots were identified by two-dimensional electrophoresis (2-DE) gels. 44 spots showed significant expression changes based on induction factor, which 7 spots were recognized significantly at 5% probability level. 1 and 6 spots were up and down-regulated, respectively. By using LC-MS/MS mass spectrometry analysis proteins that involved in energy production and photosynthesis were identified. Role of these proteins to salt stress response will be discussed.